1H NMR-based metabonomic analysis of serum and urine in a nonhuman primate model of diabetic nephropathy - Liu, J.; Wang, D.; Chen, Younan; Sun, H.; He, S.; Wang, C.; Yang, G.; Shi, M.; Zhang, J.; Ren, Y.; Wang, L.; Lu, Y.; et al. (2013)
Diabetic nephropathy (DN) is a serious metabolic disease, and comprehensive understanding of its complex mechanism will help in preventing the onset and progression of DN. To reveal the systemic metabolic changes associated with renal injury, we performed 1H NMR-based metabonomic and multivariate analyses to analyze serum and urine obtained from a nonhuman primate model of DN. Our results indicated that DN monkeys exhibited a distinct metabolic profile, including higher levels of VLDL/LDL, lipids, unsaturated lipids, uric acid, allantoin, fumarate and hippurate, as well as lower levels of HDL, alanine, glutamate, pyruvate, formate, tyrosine, histidine and NAD+. The disturbed metabolic pathways were further identified, including NAD + metabolism, purine metabolism, oxidative stress, lipid metabolism, and renal tubular reabsorption. This study highlights that NMR-based metabonomics provides insight into the underlying pathways in the pathogenesis and progression of DN at the metabolic level.